A Novel Technique for Keyhole-Less Reinforced Friction Stir Spot Welding of Polyethylene Sheets - Moosa Sajed; S. M. Hossein Seyedkashi (International Journal of Advanced Design and Manufacturing Technology, 2019)
Two main problems exist with friction stir spot welded joints; remaining of a keyhole after welding and low strength of joints. In this paper, a novel method is proposed to address both problems in a simple and cost-effective way. This process is named “Reinforced Friction Stir Spot Welding” or “RFSSW” which is based on recently introduced “TFSSW” process. SiC powder was added to the friction stir spot joints of polyethylene sheets with a thickness of 3 mm. First, the sheets were welded using conventional friction stir spot welding tool with a cylindrical pin. Then, the keyhole was filled with SiC powder. In the second stage, for stirring of SiC particles in the nugget and refilling the keyhole as well, a pinless tool was utilized. A homogenized distribution of reinforcing powder was obtained in the nugget. The effect of welding parameters including refilling tool shoulder diameter, refilling dwell time, and refilling tool rotational speed were evaluated in both TFSSW and RFSSW. In both processes, the refilling tool shoulder diameter was the most effective parameter. The strength was increased by 40% applying TFSSW and a further increase by 20% was obtained by reinforcing. Optimized parameter levels are refilling tool shoulder diameter of 24 mm, refilling tool rotational speed of 800 rpm, and refilling dwell time of 50s which result in shear strength of 1079 N.